2014
DOI: 10.1093/hmg/ddu242
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the retinitis pigmentosa 28 gene Fam161a in mice affects photoreceptor ciliary structure and leads to progressive retinal degeneration

Abstract: Mutations in the FAM161A gene were previously identified as the cause for autosomal-recessive retinitis pigmentosa 28. To study the effects of Fam161a dysfunction in vivo, we generated gene-trapped Fam161a(GT/GT) mice with a disruption of its C-terminal domain essential for protein-protein interactions. We confirmed the absence of the full-length Fam161a protein in the retina of Fam161a(GT/GT) mice using western blots and showed weak expression of a truncated Fam161a protein by immunohistochemistry. Histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
60
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 44 publications
13
60
2
1
Order By: Relevance
“…Our study shows that mutation of a single glycylase gene, Ttll3, is sufficient to induce slow retinal degeneration in mice, as revealed by shortened connecting cilia (Karlstetter et al, 2014), a massive activation of Müller glia, indicative of retinal stress (Honjo et al, 2000;Iandiev et al, 2006), and a remarkable increase of photoreceptor apoptosis. The degeneration could be related to a partial dysfunction of the IFT in the connecting cilia, which is considered a possible cause of retinal degeneration (Alfinito and Townes-Anderson, 2002;Boubakri et al, 2016;Bujakowska et al, 2015;Hollingsworth and Gross, 2012;Jiang et al, 2009).…”
Section: Research Articlementioning
confidence: 75%
See 1 more Smart Citation
“…Our study shows that mutation of a single glycylase gene, Ttll3, is sufficient to induce slow retinal degeneration in mice, as revealed by shortened connecting cilia (Karlstetter et al, 2014), a massive activation of Müller glia, indicative of retinal stress (Honjo et al, 2000;Iandiev et al, 2006), and a remarkable increase of photoreceptor apoptosis. The degeneration could be related to a partial dysfunction of the IFT in the connecting cilia, which is considered a possible cause of retinal degeneration (Alfinito and Townes-Anderson, 2002;Boubakri et al, 2016;Bujakowska et al, 2015;Hollingsworth and Gross, 2012;Jiang et al, 2009).…”
Section: Research Articlementioning
confidence: 75%
“…As shortening of connecting cilia could be a sign of retinal degeneration (Karlstetter et al, 2014), we analysed retinas of Ttll3 −/− mice for signs of degeneration. First, we determined the distribution of rhodopsin in retina sections of 12-month-old mice.…”
Section: Glycylation Controls the Length And Functionality Of Photorementioning
confidence: 99%
“…We have previously characterized the macrophage/microglia WAP domain protein (AMWAP) as a regulator of pro-inflammatory response 37,38 . AMWAP transcription is rapidly induced in microglia from different retinal disease mouse models, including inherited photoreceptor dystrophies and different light challenge paradigms 7,32,33,39 . Another good marker to detect microglia reactivity is CCchemokine ligand 2 (CCL2, alias monocyte chemoattractant protein 1, MCP-1), which has a key role in pro-inflammatory mononuclear phagocyte chemotaxis and migration in the retina 14,40 .…”
Section: Development Of the Protocolmentioning
confidence: 99%
“…4 Although it has been shown that FAM161A is required for routing of outer segment proteins, such as opsin and rds/peripherin 2, its precise function remains unclear. 6,7 We aimed to gain insights into the frequency of FAM161A mutations in patients with RP seen at a single UK centre and to characterise the retinal phenotype in individuals with FAM161A-related disease.…”
Section: Introductionmentioning
confidence: 99%